Plan de mejoramiento empresarial a Droguerías Profamiliar Armenia - Quindío (2015)
Profamiliar drugstores SAS, a company created 30 years ago in the city of Armenia - Quindío, founded by Gildardo Cuellar and Maria Eugenia Montes, starting work with an activity of distribution of pharmaceuticals, cosmetics and popular consumption, with high market recognition pharmacist and the general public, but due to indiscriminate proliferation of Drugstores, they have triggered different symptoms like decline in sales and a loss in market share. For this reason, the interest generated by their owners, financial performance and increase their trade beyond the current and in turn further progress have to innovate to support the recognition given you the service provided. Based on the analysis of SFAS matrix for each of the business areas, weaknesses and threats, some of the opportunities and strengths that should be given continuity to implement key strategies in an improvement plan were determined in order to carry out the most important fixes that the company does not apply to your current administrative model, therefore, the failure to establish a clear organizational structure, lack of training and motivation of employees and the decrease in generating profits has led the company to seek an immediate solution. Following these parameters improvement plan focused on creating new services that seek to increase market share, increased profits and company growth by offering new spaces and products to customers, and improvements in the administration named above are fundamental to the organization therefore the company recommends a number of strategies to meet.